Moral Certainty instead of Moral Objectivity - Noreikaitė, Aistė (Problemos, 2024)
This paper argues that although Dworkin’s aim of developing a more practical understanding of moral truth is plausible, his attempt to do that while keeping the concept of moral objectivity remains deeply problematic. Because of its opposition to everything subjective, moral objectivity stands in an inherent conflict with the practical reality that we experience as persons from a first-person perspective; therefore, Dworkin’s attempt to reconceptualize moral objectivity from within a first-person perspective is inherently contradictory. The paper suggests that we should go one step further than Dworkin and give up the concept of moral objectivity altogether. A notion of moral certainty instead of moral objectivity would satisfy Dworkin’s intention of finding a practical conception of moral truth more adequately. A brief preliminary conception of it is developed while invoking the German philosopher Robert Spaemann’s ontology of a person.